Differences in the incidence and clinical outcomes of SARS-CoV-2 infection between Italian and non-Italian nationals using routine data. (October 2022) - Fabiani, M.; Vescio, M.F.; Bressi, M.; Mateo-Urdiales, A.; Petrone, D.; Spuri, M.; Sacco, C.; Del Manso, M.; Bella, A.; D'Ancona, F.; Rota, M.C.; Filia, A.; et al.
Abstract: Objectives: This study was to compare the incidence and clinical outcomes of SARS-CoV-2 infection between Italian and non-Italian nationals. Study design: We retrospectively analysed data from the COVID-19 Italian integrated surveillance system (14 September 2020 to 17 October 2021). Methods: We used multivariable Cox proportional hazards models to estimate the hazard ratio (HR) of infection and, among cases, the HRs of death, hospitalisation and subsequent admission to intensive care unit in non-Italian nationals relative to Italian nationals. Estimates were adjusted for differences in sociodemographic characteristics and in the week and region of diagnosis. Results: Of 4, 111, 067 notified cases, 336, 265 (8.2%) were non-Italian nationals. Compared with Italian nationals, non-Italians showed a lower incidence of SARS-CoV-2 infection (HR = 0.81, 95% confidence interval [CI]: 0.80–0.81). However, once diagnosed, they were more likely to be hospitalised (HR = 1.90, 95% CI: 1.87–1.92) and then admitted to intensive care unit (HR = 1.08, 95% CI: 1.04–1.13), with differences larger in those coming from countries with a lower human development index. Compared with Italian cases, an increased rate of death was observed in non-Italian cases from low–human development index countries (HR = 1.41, 95% CI: 1.23–1.62). The HRs of SARS-CoV-2 infection and severe outcomes slightly increased after the start of the vaccination campaign. Conclusions: Underdiagnosis and delayed diagnosis in non-Italian nationals could explain their lower incidence compared with Italians and, among cases, their higher probability to present clinical conditions leading to worse outcomes. Facilitating early access to vaccination, diagnosis and treatment would improve the control of SARS-CoV-2 transmission and health outcomes in this vulnerable group.